2014
DOI: 10.1088/0029-5515/54/7/073014
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of neoclassical toroidal viscosity with a particle simulation in the tokamak magnetic braking experiments

Abstract: Accurate calculation of perturbed distribution function δf and perturbed magnetic field δB is essential to achieve prediction of non-ambipolar transport and neoclassical toroidal viscosity (NTV) in perturbed tokamaks. This paper reports a study of the NTV with a δf particle code (POCA) and improved understanding of magnetic braking in tokamak experiments. POCA calculates the NTV by computing δf with guiding-center orbit motion and using δB from the ideal perturbed equilibrium code (IPEC). POCA simulations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…He showed that the particle orbit code for anisotropic pressure (POCA) code, which resolves complexities of guiding-center particle motions [51], may provide a first-principles solution to NTV beyond the semi-analytic approximation. Moreover, the IPEC code may provide a 3D perturbed equilibrium and magnetic field structure based on the ideal plasma response [52]. He showed from simulations that a realistic tracking of guiding-center particle orbits and the 3D equilibrium with plasma responses are of importance for an accurate description of toroidal momentum transport in the presence of 3D fields.…”
Section: Progress In Rmp and Elm Physics Studiesmentioning
confidence: 99%
“…He showed that the particle orbit code for anisotropic pressure (POCA) code, which resolves complexities of guiding-center particle motions [51], may provide a first-principles solution to NTV beyond the semi-analytic approximation. Moreover, the IPEC code may provide a 3D perturbed equilibrium and magnetic field structure based on the ideal plasma response [52]. He showed from simulations that a realistic tracking of guiding-center particle orbits and the 3D equilibrium with plasma responses are of importance for an accurate description of toroidal momentum transport in the presence of 3D fields.…”
Section: Progress In Rmp and Elm Physics Studiesmentioning
confidence: 99%
“…In one approach [49], the POCA (Particle Orbit Code for Anisotropic Pressure) code was developed to follow guiding centre orbits of particles for precisely calculating δf , the perturbed distribution function, in a non-axisymmetric ideal MHD equilibrium determined by IPEC [50]. POCA simulations show the importance of collisionality and particle resonances with the toroidal rotation, similar to that found for RWMs.…”
Section: Non-inductive Sustainment: Stable Operationsmentioning
confidence: 79%
“…Such further development can build upon the significant existing literature on NTV (e.g., Refs. [16][17][18][19][20][21][22][23][24][25][26][27][28] to represent the radial magnetic fields produced by field ripple, instabilities, field error, etc., and to model various mechanisms for producing parallel viscosity (i.e., for modeling g 0 ).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…16,[21][22][23][24] Various specific axisymmetric and nonaxisymmetric coordinate systems can be found in the literature. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]…”
Section: Coordinate Systemmentioning
confidence: 99%